2013
DOI: 10.4414/smw.2013.13759
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts in the county of Basel: results from the WHO/EURO Multicentre Study on Suicidal Behaviour

Abstract: This study offers the first published representative data of an entire Swiss county. Established sociodemographic and clinical risk factors for suicide attempts were reproduced. The identification of risk factors contributes to developing local targeted prevention strategies, for example education of risk groups and caregivers, and pharmacolegal consequences for package sizes. Gender- and age-specific prevention and aftercare programmes are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 90 publications
8
23
0
1
Order By: Relevance
“…Our results are in line with such findings, showing higher prevalence rates of suicide attempts among women (8.1%) than men (5.1%), whereas the rates for suicidal ideation were almost identical (42.2% vs. 38.8%). A recent study of Muheim et al [23] also found nearly twice as many suicide attempts in women than in men with a peak between ages 20-24 years. Our prevalence rate of 6.6% for suicide attempts (women and men) ranks between the 4.1% found in the NCS-A study of adolescents in the USA [24] and the 8.2% reported among 36757 17 year-olds in France [25].…”
Section: Discussionmentioning
confidence: 98%
“…Our results are in line with such findings, showing higher prevalence rates of suicide attempts among women (8.1%) than men (5.1%), whereas the rates for suicidal ideation were almost identical (42.2% vs. 38.8%). A recent study of Muheim et al [23] also found nearly twice as many suicide attempts in women than in men with a peak between ages 20-24 years. Our prevalence rate of 6.6% for suicide attempts (women and men) ranks between the 4.1% found in the NCS-A study of adolescents in the USA [24] and the 8.2% reported among 36757 17 year-olds in France [25].…”
Section: Discussionmentioning
confidence: 98%
“…Psychiatric disorder, especially depression, has been found to be present in up to 90% of those who complete suicide (Cavanagh et al, 2003), and it has been argued that this figure, though high, is an underestimate (Ernst et al, 2004;Flavio et al, 2013;Zhang & Li, 2013). Other factors associated with suicide are physical ill-health, male gender (though the opposite is true in DSH), older age, living alone, recent major life events, childhood maltreatment, alcohol misuse, and increased hopelessness (Hawton & van Heeringen, 2009;Nock et al, 2008).…”
Section: Risk Factors For Suicidementioning
confidence: 99%
“…Further sources were the Psychiatric University Clinics as the main psychiatric treatment center in the area, the hospitals surrounding Basel-City, and all psychiatrists in private practice in Basel-City. All of these sites were already referring patients to the clinical epidemiological WHO/EURO Multicentre Study on Suicidal Behavior (Muheim et al, 2013); hence, a mechanism for recruitment was already established and functioning effectively at the beginning of the current study.…”
Section: Methodsmentioning
confidence: 99%
“…For patients who declined participation or who did not show up for the scheduled interview, at minimum sociodemographic and basic clinical data, which were recorded for the WHO/EURO Multicentre Study and which did not rely on informed consent and participation of the patient (Muheim et al, 2013), were available and were used for comparison with our study group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation